THE PRESENCE OF DISSOLVED ANIONS IN SEVERAL WELL WATER SAMPLES FROM NADĂŞ VILLAGE (CLUJ COUNTY) - NICOARĂ, Carla; PIŞTEA, Ioana; ROBA, Carmen Andreea; ROȘU, Cristina (Studia Universitatis Babeș-Bolyai Ambientum, 2023)
The main objective of the present study was to determinate the quality of well water by analyzing the presence of dissolved anions from several well water samples from a rural area. The samples were taken from Nadăş village, located in Crisul Repede village, Cluj County. At the beginning of the study there were 17 wells selected, but only 10 private wells have been chosen (W1, W3, W4, W5, W6, W7, W12, W13, W15, W16) for the analysis of dissolved anions content: F-, Cl-, NO3-, NO2- , PO4-3, SO4-2. The wells were selected according to the electrical conductivity (EC) values that ranged between 409 μS/cm (W12) and 1251 μS/cm (W4). EC was within the MPL (maximum permissible limit) set by national legislation which is 2500 μS/cm. In the water samples taken from W1, W5, W6, W7 nitrate exceeded the MPL (50 mg/ L according to the national legislation). In the water sample from W6 nitrite exceeded the MPL (0.5 mg/ L according to the national legislation). In the water sample from W1 sulphate exceeded the MPL (250 mg/ L according to the national legislation). The present study indicated that some of the investigated water sources may pose some health problems if the waters are used as drinking water, especially due to the high content of nitrate and nitrite.